Relationship between extraversion and the effectiveness in managing people. - Tan, Ying Hui. (2008)
This study extends theory and research on the relationship between extraversion and leadership effectiveness, done in the context of Singapore for the first time. The effect of transformational leadership style is also examined in this relationship.